Introduction to actinic damage and actinomycetes as a promising source for eco-friendly photoprotective compounds: Introducción al daño actínico y los actinomicetos como fuente prometedora de compuestos fotoprotectores ecológicos (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
The use of sunscreens is a fundamental strategy of an effective photoprotection scheme. Currently, several ultraviolet (UV) filters have been questioned for their side effects, mainly those that harm the environment. Therefore, there is a demand to find compounds with photoprotective properties. In this regard, natural products have traditionally been a promising source of compounds with diverse biological activities, including those related to photoprotection. Recently, natural microbial products have shown very promising opportunities supported by biotechnological advances, including those possibilities opened up by computer-aided tools. Under this scenario, several studies have recognized the great potential of the phylum Actinomycetota as a source of compounds with photoprotective properties. This review examines how solar radiation induces skin photodamage, explores existing photoprotection strategies, and highlights the immense potential that lies in the specialized metabolism of actinomycetes. These microorganisms offer a rich and untapped vein for the development of innovative products that could transform the sun protection industry.
Keywords: Photodamage; Sunscreen; Natural Products; Actinomycetota; Actinobacteria